Analysis of Indications and Results of Anorectal Manometry in Two Tertiary Hospitals in India - Rajiv Baijal; Mayank Jain (Archives of Clinical Gastroenterology - Peertechz Publications, 2017)
The anorectum plays an important role in regulation of defecation and in maintenance of continence [1]. The most widely used test for anorectal function is anorectal manometry. It measures pressures of the anal sphincter muscles, sensation in the rectum, and neural refl exes that are needed for normal bowel movements. This test is mainly used in evaluation of constipation, fecal incontinence, anal sphincter tone, functional anorectal pain, pelvic fl oor dyssynergia and diagnosis of Hirschsprung's Disease [2].  Parameters studied by anorectal manometry are the rectoanal inhibitory refl ex, anal resting pressure, sustained voluntary contraction of anal canal and rectal sensation [3]. Anorectal manometry is now available at multiple centres in India. However, the awareness regarding the procedure and its uses is limited. This study was done with the aim to analyse the indications for referral and results of anorectal manometry in two teaching hospitals in India.